Color Psychology in Video Games: A Systematic Literature Review - Terron-Lopez, Pilar; Castilla Cebrián, Guillermo (VISUAL REVIEW. International Visual Culture Review / Revista Internacional de Cultura Visual, 2025)
The video game industry is expanding, and it is necessary to determine if color psychology applies to its graphical interface. The main objective is to understand how the use of color psychology in video games has been studied. This study conducts a systematic review of color theory and its impact on the graphical interface. Existing studies highlight the role of color in communicating with users and enhancing game mechanics and narratives. This proposal recommends standardized criteria for evaluating color psychology in video games.